Molecular detection of virulence genes in Salmonella spp. isolated from chicken faeces in Mafikeng, South Africa - Tsepo A. Ramatla (Journal of the South African Veterinary Association, 2020)
Chickens have been implicated in most Salmonella disease outbreaks because they act as carriers of the pathogen in their gut. There are over 2500 serotypes of Salmonella that have been reported worldwide and 2000 of these serovars can be found in chickens. The main objective of this study was to determine the Salmonella serotypes found in poultry farms around Mafikeng district, South Africa. Salmonella was identified according to the guidelines of the International Organization for Standardization (ISO) (ISO 6579:2002) standard techniques. Faecal samples were collected and analysed for Salmonella using conventional cultural methods and polymerase chain reaction targeting the 16S Ribosomal Deoxyribonucleic acid (rDNA) gene for Salmonella identification. Out of 130 presumptive Salmonella isolates determined by urease and triple sugar iron tests, only 46 isolates were identified as Salmonella serotypes of which S. Typhimurium was the most frequent with 18 (39.1%), followed by S. Heidelberg with 9 (19.6%), S. bongori with 7 (15.2%), S. Enteritidis with 6 (13.0%) and both S. Paratyphi B and S. Newport with 3 (6.5%) each. Seven virulence genes including invA 100%, spy 39%, hilA 9%, misL 30%, sdfI 13%, orfL 11% and spiC 9% were detected from these Salmonella isolates in this study. The presence of these virulence genes indicates high pathogenicity potential of these isolates which is a serious public health concern because of zoonotic potential of Salmonella.